A closed-loop high temperature superconducting magnet energized by flux pump and its piecewise semi-analytical solution. (1st July 2022) - Zhu, Lingfeng; Wang, Yinshun; Zhang, Xindan; Wang, Lecheng
Abstract: High temperature superconducting (HTS) magnets energized by flux pumps can carry heavy current without heat leakage from current leads and are therefore appropriate for a wide range of applications. However, the soldering resistance remains an obstacle to the persistent operations of the HTS magnets. Here, we propose a closed-loop HTS magnet magnetized by flux pump with thermal switches. The magnet consists of a closed-loop single pancakes (SPs) coil wound by a rare-earth barium copper oxide (REBCO) tape on which a slit is cut to form a closed-loop ring within which current can flow without encountering the soldering resistance. Another REBCO tape is soldered on the closed-loop ring to form a pump bridge and a flux pump consists of a copper coil with iron core is installed around the pump bridge. There exists a group of manganese copper wires wound on the closed-loop ring and the pump bridge respectively as thermal switches. A piecewise semi-analytical solution is suggested to investigate the charging process by which the transport current in the magnet is calculated. Experiments are carried out to verify the feasibility of the magnet and the solution. The results show that the magnet can be operated in a persistent current mode, and thus, this study represents a practical solution for persistent operation of the HTS magnets. Besides, the proposed solution can effectively explain and predict the saturation current of the suggested magnet, which can, therefore, guide the design of other forms of HTS magnets and flux pumps.